Analisis Konsentrasi pH dan Aluminium dari Air Minum Olahan Rumah Tangga di Kost X dan Kost Y Kota Batam - Roselyn Indah Kurniati; Lina Hanarisanty (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
The availability of water resources and the demand for drinking water must be managed effectively. Poor drinking water quality will cause adverse effects on humans. This study aims to determine the pH and aluminum parameters of the processed independent drinking water in Kost X and Kost Y Batam City. The research was conducted by taking drinking water samples in 2 locations, Kost X and Kost Y, 6 times within 6 months. Aluminum concentration analysis refers to Standard Methods for the Examination of Water and Wastewater (2017) and pH using a pH meter directly after sampling. The analysis results obtained were compared with the Regulation of the Minister of Health of the Republic of Indonesia Number 492/Menkes/Per/IV/2010 concerning Drinking Water Quality Requirements, which is 0.2 mg/L for aluminum and pH 6.5-8.5. The results of the pH concentration analysis in Boarding House X ranged from 7.1-8.4 and Boarding House Y ranged from 6.8-7.9, while the results of the aluminum concentration analysis in Boarding House X ranged from 0.08-0.102 mg/L and in Boarding House Y ranged from 0.093- 0.112 mg/L. The results showed that the pH and aluminum concentrations have not exceeded the standard based on Permenkes No. 492 of 2010.